Transformasi Digital Pelayanan Kesehatan di RSUD Siti Fatimah Sumatera Selatan untuk Peningkatan Pelayanan Prima - Chendra, Rudy; Sriati, Sriati; Putra, Raniasa (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
Digital transformation in health services is an urgent need in the modern era, especially in increasing efficiency, transparency, and community satisfaction. This research aims to develop a digital transformation model at Siti Fatimah Hospital in South Sumatra by integrating aspects of continuous training to realize excellent service. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation studies. The results of the study show that even though the hospital has implemented the Hospital Management Information System (SIM-RS), various challenges, such as limited infrastructure, low digital literacy, and system fragmentation, still hinder the effectiveness of the transformation. Great opportunities remain open, especially in strengthening data-driven decision-making and expanding digital services to patients. The proposed ideal model includes five main components: digital leadership, continuous training, digital culture, collaborative systems, and an excellent service framework. This model emphasizes the importance of a holistic approach that combines technology, people, and public service values to create adaptive and inclusive health services.